The effects of Brazil’s family health strategy on educational outcomes - Costa, Gabriel Weber (2018)
We aim to evaluate the effects of Brazil’s Family Health Strategy (FHS), a large-scale community-based health intervention, on educational outcomes during primary and secondary education.We use student-level data and adopt a differences-in-differences approach that explores timing of program implementation across municipalities and students’ year and location of birth to estimate FHS effects on enrollment flow, school delay, and Mathematics and Portuguese performance. Results suggest that FHS implementation is associated with an increased probability that students stay in school after age 7 and a decreased probability that students are delayed by two or more grades, although the latter seems to fade after age 12. Estimates for student performance indicate that the program decreases test scores, although these estimates could be affected by compositional changes in treatment and control groups. We also find evidence that program effects are stronger when time of exposition is increased, which is consistent with the FHS continuous expansion over time and with previous research.